Mutations Decreasing Intrinsic β-Lactam Resistance Are Linked to Cell Division in the Nosocomial Pathogen Acinetobacter baumannii - Knight, Daniel (Antimicrob Agents Chemother, 2016)
Transposon mutagenesis was used to identify novel determinants of intrinsic β-lactam resistance in Acinetobacter baumannii. An EZ-Tn5 transposon insertion in a gene corresponding to the A1S_0225 sequence resulted in a 4-fold decrease in resistance to ampicillin, cefotaxime, imipenem, and ceftriaxone but did not alter resistance to other classes of antibiotics. Based on this phenotype, the gene was designated blhA (β-lactam hypersusceptibility). The blhA::EZ-Tn5 mutation conferred a similar phenotype in A. baumannii strain ATCC 17978. The wild-type blhA gene complemented the blhA::EZTn5 insertion and restored β-lactam resistance levels back to wild-type levels. The blhA mutation also increased β-lactam susceptibility in an adeB adeJ double mutant, indicating that the blhA mutation acted independently of these efflux systems to mediate susceptibility. In addition, mRNA levels for the bla(OXA) and bla(ADC) β-lactamase genes were not altered by the blhA mutation. The blhA mutation resulted in a prominent cell division and morphological defect, with cells exhibiting a highly elongated phenotype, combined with large bulges in some cells. The blhA gene is unique to Acinetobacter and likely represents a novel gene involved in cell division. Three additional mutations, in zipA, zapA, and ftsK, each of which encode predicted cell division proteins, also conferred increased β-lactam susceptibility, indicating a common link between cell division and intrinsic β-lactam resistance in A. baumannii.